Analysis of motivational factors influencing the performance of municipal government employees in public service delivery the case of two selected metropolitan municipalities in Thailand - Sonsri, Gamolporn; Legaspi, Perla E. (2005)
The study concerns itself with the state of service delivery of local governments in Thailand, in particular the municipal government's performance inthe delivery of public health and sanitation services. One angle to find out such state of service delivery is to know the motivational factors of employees and thus be able to assess and evaluate the extent that the motivational factors under study influence employeess to perform better in the delivery of such services. The important point is that if these motivational factors are determined as well as their influences on performance, then the road to better service delivery to the people will not be far behind...
"October 2005."
Thesis (D. Public Administration)--University of the Philippines Diliman.
Keywords: Public health -- Thailand -- Employees; Public health -- Thailand -- Evaluation; Sanitation -- Thailand -- Evaluation; Municipal government -- Thailand -- Evaluation; Public administration -- Thailand -- Evaluation; Thailand -- Officials and employees -- Evaluation